On the Haar and Walsh Systems on a Triangle (Journal of Computational Mathematics, 1983)
In this paper we establish the Haar and Walsh systems on a triangle. These systems are complete in $L_2(Δ)$. The uniform convergence of the Haar-Fourier series and the uniform convergence by group of the Walsh-Fourier series for any continuous function are proved.